Corrosion Behavior of Zinc Wrought Alloy ZnAl15Cu1Mg (ZEP1510) as a Potential Substitute for Brass and Galvanized Steel - Abdulkerim Karaman; Alexander Kremer; Michael Marré (Alloys)
The increasing restriction of lead in industrial alloys, particularly in copper–zinc-based materials such as CuZn40Pb2, necessitates the development of environmentally safer alternatives. ZnAl15Cu1Mg (ZEP1510), a zinc-based wrought alloy composed of 15% aluminum, 1% copper, 0.03% magnesium, with the remainder being zinc, has emerged as a promising candidate for lead-free applications due to its favorable forming characteristics and corrosion resistance. This study investigates the performance of ZEP1510 compared to conventional leaded copper alloys and galvanized steel. Corrosion behavior was evaluated using neutral salt spray testing, cyclic climate chamber exposure, and electrochemical potential analysis in chloride- and sulfate-containing environments. ZEP1510 exhibited corrosion resistance comparable to brass and significantly better performance than galvanized steel in neutral and humid atmospheres. Combined with its low processing temperature and high recyclability, ZEP1510 presents itself as a viable and sustainable alternative to brass with lead for applications in sanitary, automotive, and electrical engineering industries.